Concentration and Diversification of Production by Example of Major Indian Business groups - M. A. Vorobyeva (Vestnik MGIMO-Universiteta)
The goal of this work is to show that in contrast with the dominating economic concept, that concentration and expansion of production in one or several neighboring industries is the natural and economically reasonable mechanism for business growth, there is an alternative model of big business development, such as the industrial diversification. In this paper we analyze the phenomenon of big capital diversification on example of Indian business groups. We assume that diversification appears to be a necessary, and sometimes the only possible way of big business development amid imperfect market competition, inherent in emerging markets. We show that the main feature of big business formation in India, due to some conditions of colonial and postcolonial development, is that capital concentration was not accompanied by industrial concentration. The factors which condition the absence of industrial concentration in the Indian business groups are: the activity of managing agencies and other specifics of primitive capital accumulation, state regulations and licensing policy, state limitations on the scale of production, tough Monopoly Act, various market distortions etc. The paper also postulates that heterogenic industrial structure predetermines organizational and managerial forms big business takes. It resumes that industrial diversification enables big business to better adjust to market and legal imperfections as well as to hedge transnationalisation risks. As a business strategy diversification is common not only to India, but to other big vibrant rapidly developing economies. The success of Asian and Latin American business groups and conglomerates is worthy of a comprehensive investigation to adopt their experience in Russia.